(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: Corporate Social Responsibility (CSR) refers to the obligations of an organization concerned towards the society. It entails the efforts by a company to improve the society in a way that our community is benefited economically, socially in order to improve the standard of living. CSR has been practiced by companies of all the sectors for decades voluntarily around the world. Objectives: The study identified CSR practiced in Hotels of India and sensitized hospitality students regarding CSR. Methodology: The study entailed a quantitative as well as a qualitative research design. For determining the CSR practices of eight hotels data collection was done through official websites of the hotel. The Sensitization was conducted for thirty two hospitality students on the basis of convenience sampling technique through a powerpoint presentation followed by an online quiz. The locale for sensitization was Institute of Hotel Management, Catering & Nutrition, Pusa, New Delhi. The results of the sensitisation were analysed through calculation of mean, median, range and percentage analysis. Results: The findings of the present study revealed that every hotel brand had adopted and practices their own set of activities for doing CSR. CSR was done for the members of the society, environment and promoting culture and heritage of our country through artisans. The Sensitization session results revealed that every respondent was able to score more than 60 points in the online quiz. The mean for the points scored by the respondents was 85.63 points. The median score was 80 points and the range of the points scored was 60-100 points. Conclusion: The course curriculum for Hospitality students should also be incorporated with brief and vibrant ideas of CSR which students can start imbibing in their practices from their academics and try to incorporate in future when they join the hospitality industry. CSR activities and Hospitality students for sure with this culture going to improve the society overall and bring a bright future for our country.